(untitled) (Al-Academy, 2024)
The study dealt with the concept of perception and attention and its impact on the design idea based on modern scientific theories and opinions and reading the design idea with the concept of motivational and therapist perception and the sense of the motor and formal place and organizing the behavioral response in the analysis and interpretation of the idea, color and function and addressing that with scientific theories and the relationship of the inside with the outside and normal human behavior in his daily social and practical life Through the golden theory, the Gestalt theory, the phenomenological theory, and the organic theory are among the theories of perception, which is the means by which a person communicates with his surrounding environment and works on accumulating experiences and mental perceptions of the elements and composition of design from the heart of the need and the idea based on the psychology of the psychological theory of the recipient through the feeling of being inside space and its contents and realizing Shapes, colors, and movable and fixed architectural elements as an architectural entity that exists through the eye’s network and other senses, that is, there are main functions of the mind that are perception, understanding, and listening that realize the assets around us in our daily lives. Attention is a perceptive process that helps avoid mistakes at the right time by being aware of the responses of ideas and the influencing external factors.